PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON PADA PELAJARAN SENI RUPA DI KELAS IV SDS PANCA BUDI MEDAN - Shabina Dinisyah Fajar, Natasya; Afriadi, Putra; Winara, Winara; Wahyu Purnomo, Try; Mustika Aulia, Sri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to determine the validity, practicality, and effectiveness of powtoon-based learning media in fine arts lessons in grade IV of SDS Panca Budi Medan. The learning media developed uses the ADDIE development model which includes analysis, design, development, implementation, and evaluation, especially material for drawing sketches of flora and fauna for grade IV students in the even semester of the 2024/2025 school year. A total of 20 grade IV students were involved as research subjects, along with two experts to test the validity of the media and one teacher to test the practicality of learning media in fine arts subjects in accordance with the independent curriculum. The validation results from the material experts showed a high score, namely 89 out of 110 scores with a percentage of 89%, while media design experts gave a score of 68 out of a maximum score of 75 with a percentage of 90.6%. Teachers also gave a high score on the practicality test with a score of 54 out of a total of 60, resulting in a percentage of 90%, where all aspects, such as appearance, presentation, material, and language, obtained the categories of